Comparative Analysis of Collagen Supplementation Forms and Their Effects on Multiple Health Parameters - Siemiątkowski, Robert; Haber, Mateusz; Czachor, Adrianna; Kula, Paula; Juśkiewicz, Adam; Grelewicz, Olga; Kucy, Natalia; Servaas, Elwira; Kotula, Alicja (Journal of Education, Health and Sport, 2024)
Collagen, a key structural protein, is essential for maintaining the integrity of connective tissues such as skin, cartilage, tendons, bones. As natural collagen production decreases with age and is further compromised by environmental factors such as UV radiation and poor diet, collagen degradation accelerates, leading to conditions like wrinkles, joint stiffness, and decreased bone density. Collagen supplementation has gained widespread attention as a therapeutic intervention to counteract these effects. This review conducts a comprehensive comparative analysis of various forms of collagen supplementation, including hydrolyzed collagen, undenatured collagen, and gelatin, and their effects on a range of health outcomes. Hydrolyzed collagen, due to enhanced bioavailability, is associated with improvements in skin elasticity, hydration, joint pain relief, and muscle recovery, making it particularly valuable for aging populations and athletes. Undenatured type II collagen, on the other hand, modulates immune responses and shows potential in reducing inflammation and slowing the progression of degenerative joint diseases such as osteoarthritis and rheumatoid arthritis. Gelatin, while less bioavailable than hydrolyzed collagen, still supports skin and joint health when taken in larger quantities. This review also explores emerging evidence of collagen’s beneficial effects on bone density, wound healing, and hair health, with marine-derived collagen showing promise in skin health due to its rapid absorption. Potential adverse effects, including mild gastrointestinal discomfort and rare allergic reactions, are discussed, emphasizing the importance of sourcing high-quality products. Overall, collagen supplementation, particularly hydrolyzed collagen peptides, offers significant therapeutic potential for improving skin, joint, and musculoskeletal health, but further research is required to define optimal dosages, formulations, and long-term safety for various populations.